1987
DOI: 10.1038/329248a0
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination between antibodies to HIV and to related retroviruses using site-directed serology

Abstract: Human immunodeficiency virus (HIV) strains can be separated into two types: HIV and HIV-related West African viruses. Site-directed serology using synthetic peptides offers possibilities for the determination of type-specific antibodies. A 22-amino-acid peptide with the sequence Ala-Ile-Glu-Lys-Tyr-Leu-Glu-Asp-Gln-Ala-Gln-Leu-Asn-Ala-Trp-Cys-Ala-Phe-Arg-Gln - Val-Cys representing a conserved region of the transmembranous protein of simian T-cell lymphotropic virus-type III (STLV-III; related to West African HI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 21 publications
3
39
0
1
Order By: Relevance
“…The clade D peptide was used because it is the most antigenically divergent due to mutations within the cysteine loop (22). Every infected patient rapidly develops antibodies to this region (4,25,27,30). A low concentration of this mixture should allow the binding of late antibodies that have acquired sufficient avidity and thus quantitative detection.…”
Section: Methodsmentioning
confidence: 99%
“…The clade D peptide was used because it is the most antigenically divergent due to mutations within the cysteine loop (22). Every infected patient rapidly develops antibodies to this region (4,25,27,30). A low concentration of this mixture should allow the binding of late antibodies that have acquired sufficient avidity and thus quantitative detection.…”
Section: Methodsmentioning
confidence: 99%
“…The gp36 ectodomain is highly conserved and elicits a type-specific antibody response (13,33). Hence, most licensed diagnostic assays incorporate gp36-derived antigens to detect HIV-2-specific antibodies (1,4,12,28,29,38,42,45,48).…”
mentioning
confidence: 99%
“…A 22 amino acid (aa) synthetic peptide corresponding to a SIV sequence (aa 581 to 603) having 86% aa identity with the HIV-2 sequence bound 100% (20/20) of human HIV-2-positive sera and only one of 20 HIV-l-positive (Norrby et al, 1987). Using the sera of HIV-2-infected individuals and the antibody-reactive peptide scanning (Pepscan) method (Geysen et al, 1984(Geysen et al, , 1985, we identified nine antibody-binding domains of the transmembrane glycoprotein of HIV-2 (Goudsmit et al, 1989).…”
Section: F De Wolf and Othersmentioning
confidence: 99%